1995
DOI: 10.1159/000237160
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity IgE Receptor-Mediated Prostaglandin E2 Production by Monocytes in Atopic Dermatitis

Abstract: High affinity IgE receptor (Fc ε R I) expression on monocytes and its upregulation on monocytes from patients with atopic dermatitis (AD) have been recently reported. In this study, we investigated whether prostaglandin E2 (PGE2) release from AD monocytes was Fc ε R I-dependent or not. The monocytes were stimulated with anti-Fc ε RI monoclonal antibody (mAb) and anti-Fc ε RII mAb. Cross-linking of Fc ε R I, but not that of Fc ε R II induced PGE2 release from monocytes. In order to confirm that the PGE2 release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…PGE 2 synthesis is relied on intracellular COX including COX1 and COX2, which possess both fatty acid COX activity and PG hydroperoxidase activity. Although, IC/Ig-mediated the production of PGE 2 has been reported by several times (30,31), we were still amazed by the amount of PGE 2 by IC/Ig. Next, we demonstrated that IC/Ig induced the rapid and durative expression of COX1 and COX2 in macrophages, which may account for the reason why so large amounts of PGE 2 was induced.…”
Section: Discussionmentioning
confidence: 81%
“…PGE 2 synthesis is relied on intracellular COX including COX1 and COX2, which possess both fatty acid COX activity and PG hydroperoxidase activity. Although, IC/Ig-mediated the production of PGE 2 has been reported by several times (30,31), we were still amazed by the amount of PGE 2 by IC/Ig. Next, we demonstrated that IC/Ig induced the rapid and durative expression of COX1 and COX2 in macrophages, which may account for the reason why so large amounts of PGE 2 was induced.…”
Section: Discussionmentioning
confidence: 81%
“…Present evidence suggests that FcεRI on macrophages may have functional significance since in vitro cross‐linking of the receptor has been shown to be associated with sustained intracellular Ca 2+ release 9 and production of prostaglandin E 2 . 13 Additionally, FcεRI on monocytes mediating IgE‐dependent allergen‐presentations has been reported 15…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of allergen with surface‐bound IgE on these cells may result in the release of inflammatory mediators 10 . 12 , 13 In addition, IgE‐mediated allergen uptake by antigen‐presenting cells may facilitate subsequent presentation of allergen to allergen‐specific T cells 14 . 15 For these reasons, we have studied first, the kinetics of expression of mRNA for the α‐, β‐ and γ‐chains of FcεRI of the various cell‐types involved using a combination of in situ hybridization (ISH) and immunohistochemistry (IHC); second, the differences in the total number of FcεRI protein + cells after allergen challenge in the skin of atopic subjects; and third, the phenotype of the various FcεRI protein + cells using double IHC.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of AA in PGE 2 and LTB 4 metabolism and the relation to allergic inflammation (10)(11)(12)(13)(14) have led to the hypothesis that there is a dysregulation of AA metabolism in atopy (37). For example, a higher production of PGE 2 has been shown in monocytes from atopic individuals (38,39). Furthermore, reduced proliferative responses of peripheral blood mononuclear cells in adults with atopic dermatitis correlate with the IFNγ levels and are inversely related to T-cell production of IL-4 and the production of PGE 2 by monocytes (40).…”
Section: Pufa and Atopic Diseasementioning
confidence: 99%